Immediate sensitivity to structural constraints in pronoun resolution - Chow, Wing-Yee; Lewis, Shevaun; Phillips, Colin (Frontiers in Psychology, 2014)
Real-time interpretation of pronouns is sometimes sensitive to the presence of grammatically-illicit antecedents, and sometimes not. This occasional sensitivity has been taken as evidence that structural constraints do not immediately impact the initial antecedent retrieval for pronoun interpretation. We argue that it is important to separate effects that reflect the initial antecedent retrieval process from those that reflect later processes. We present results from five reading comprehension experiments. Both the current results and previous evidence support the hypothesis that agreement features and structural constraints immediately constrain the antecedent retrieval process for pronoun interpretation. Occasional sensitivity to grammatically-illicit antecedents may be due to repair processes triggered when the initial retrieval fails to return a grammatical antecedent.